Covid -19 and Sunday worship in the wake of the pandemic at Our Lady of Loreto, South Africa - Alubafi, Mathias F. (HTS teologiese studies, 2024)
Christians, and those of the Roman Catholic Church, have made significant adjustments to their participation in Sunday liturgy in the wake of the coronavirus disease 2019 (COVID-19) pandemic. This is especially the case for Catholic Christians at the ‘Our Lady of Loreto’ (OLL) Church in Kempton Park in South Africa. Sunday Church services that used to be compulsory for most Catholic families and community members, are now attended by few and in some cases none from staunch Catholic families and communities. However, this is not a new phenomenon in the Catholic Church. It signals the extent to which the COVID-19 pandemic has altered and continues to affect Christian families and their commitment to the Sunday liturgy. Drawing from qualitative interviews conducted with eight staunch Catholic community leaders of OLL Church in Kempton Park, Johannesburg, this paper explores the motivations for their continuous participation and/or non-participation in the Sunday liturgy in the wake of the pandemic. The findings reveal that certain behavioural patterns or activities associated with the COVID-19 pandemic motivate Catholic Christians and families to continue to participate and/or not participate in the Sunday liturgy.Contribution: The article explored and examined the way in which COVID-19 has affected Catholic Christians’ ability to attend Sunday liturgy. It discovered that while some Christians returned to church after the pandemic, others have continued to worship from home because of the influence of changes adopted during the pandemic.